EPQ models with production rate proportional to power demand rate, rework process and scrapped items - keshavarzfard, razieh; makui, ahmad; tavakkoli-moghaddam, reza; taleizadeh, ata allah (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
In the most of the production systems, at the end of the replenishment period, some imperfect units detected by inspection process, are reworked and the others are disposed. Constant rate of demand is one of the usual assumptions in the conventional lot sizing models. But this assumption is not suitable in many real cases. With regard to these points, this work deals with a joint problem of demand having a power pattern, production rate pro rata with demand rate, defective items, rework process and scrap items. It is assumed that a manufacturer may be faced with two scenarios: all imperfect units are recovered or a certain fraction of imperfect units are reworked and the others are disposed. Setup, holding, backordering, inspection, production, rework and disposal costs are involved in the inventory system. An algorithm is presented to optimize total inventory cost and determine the best reorder point, lot size and scheduling period. A numerical analysis is carried out to illustrate the applications of the proposed models.